Combined single-pedal and low adhesion control systems for enhanced energy regeneration in electric vehicles: Modeling, simulation, and on-field test. (15th April 2023) - Li, Shicheng; Xu, Lin; Du, Xiaofang; Wang, Nian; Lin, Feng; Abdelkareem, Mohamed A.A.
Abstract: In this paper, a single-pedal control algorithm was proposed, modeled, and theoretically analyzed to improve the driving range of electric vehicles and increase the intensity and frequency of energy regeneration. Specific analysis and strategy improvement were also conducted for the control problem under low adhesion conditions. The driving control function, economy, and control logic of the proposed single-pedal system were investigated using both simulations and real vehicle verifications under the New European Driving Cycle (NEDC). Based on simulations and real car testing, optimization of the single-pedal system under the traditional low adhesion control strategy was conducted, and then comprehensive comparisons were investigated. Results demonstrated that the proposed single-pedal control and its low adhesion condition control strategy are in line with the design requirements and effectively improved the vehicle economy, achieving a 24.9% energy regeneration rate. The optimized single-pedal low adhesion control strategy, according to the results, can effectively satisfy driving smoothness, economy, and stability under low adhesion conditions. Graphical abstract: Image 1 Highlights: A single-pedal control is proposed to improve driving range of electric vehicles. Optimal control strategy at low adhesion is studied to ensure stability and economy. Effectiveness of the control strategy is verified by simulation and real road tests. The single-pedal control achieved 24.9% energy regeneration on low-adhesion roads.